IoT Research for Smart Retail: Global Mapping 2000–2025 - Loso Judijanto (Westscience Press, 2026)
This study provides a comprehensive global mapping of IoT research in smart retail from 2000 to 2025, employing bibliometric and network analysis techniques. The research focuses on identifying key research trends, thematic clusters, geographical distributions, and technological milestones. Using data from Scopus and Web of Science, the study analyzes publication trends, citation patterns, author affiliations, and collaboration networks. The findings reveal the central role of IoT in smart retail, with significant contributions from artificial intelligence, blockchain, and energy efficiency. Additionally, the study highlights the evolving research priorities and geographic distribution, emphasizing the increasing involvement of emerging economies and regions in global research collaborations. The paper identifies critical research gaps and proposes future directions to enhance the development of smart retail systems⁠.